2006
DOI: 10.1177/08830738060210070301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Influence of Antiepileptic Therapy on Antioxidant Enzyme Activity and Lipid Peroxidation in Erythrocytes of Children With Epilepsy

Abstract: The aim of this study was to evaluate the influence of antiepileptic therapy on antioxidant enzyme activity and lipid peroxidation in the erythrocytes of children with epilepsy. For this purpose, the activity of superoxide dismutase, glutathione peroxidase, and glutathione reductase and the malondialdehyde concentration in 61 healthy children and 90 children with epilepsy were measured. The activities of all of these enzymes were insignificantly higher, whereas the malondialdehyde concentration was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Similarly, Vidya and Subramanian [32] reported that SVP-treatment was found to increase levels of malondialdhyde and hydroperoxides and decreased levels of enzymatic (superoxide dismutase [SOD], CAT, and glutathione peroxidase [GPx]) and non-enzymatic (glutathione [GSH]) antioxidants in rats. The activities of SOD, GPx, and GSH reductase were insignificantly lower, whereas the malondialdehyde concentration was insignificantly higher in the erythrocytes of children with epilepsy treated with SVP [33]. Zhang et al [34] found that the levels of malondialdehyde in neutrophils of SVP-treated patients were higher while the activities of SOD and CAT were significantly lower than the control and untreated groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Vidya and Subramanian [32] reported that SVP-treatment was found to increase levels of malondialdhyde and hydroperoxides and decreased levels of enzymatic (superoxide dismutase [SOD], CAT, and glutathione peroxidase [GPx]) and non-enzymatic (glutathione [GSH]) antioxidants in rats. The activities of SOD, GPx, and GSH reductase were insignificantly lower, whereas the malondialdehyde concentration was insignificantly higher in the erythrocytes of children with epilepsy treated with SVP [33]. Zhang et al [34] found that the levels of malondialdehyde in neutrophils of SVP-treated patients were higher while the activities of SOD and CAT were significantly lower than the control and untreated groups.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in antioxidant defence mechanisms, as a result of epileptic condition itself or the effects of antiepileptic therapy have been studied in humans, but the observed research findings are discordant [ 5 - 7 , 31 - 47 ].…”
Section: Oxidative Stress In Drug-naive Patients With Epilepsymentioning
confidence: 99%
“…Sobaniec et al and Yük-sel et al found lower levels in patients receiving VPA. 44,45 On the other hand, Kürekçi et al 46 and Cengiz et al 47 reported higher levels of GPx in patients treated with VPA. In our study, GPx activity was higher in VPA group compared with control group in lens tissue.…”
Section: Discussionmentioning
confidence: 95%